2021
DOI: 10.1371/journal.pone.0248639
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-10 in the serum and exfoliated cervical cells of patients infected with high-risk human papillomavirus

Abstract: Persistent infection by high-risk human papillomavirus (HR-HPV) is the main cause of cervical cancer and its precursor lesions. While some cytokines help immune cells in virus clearance, others contribute to the persistence of infection and neoplastic progression. Here, the levels of interferon (IFN)-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-10, IL-6, IL-4, and IL-2 were quantified in the serum and exfoliated cervical cells (ECCs) of patients with HR-HPV, and the presence of IL-6+ cells was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…It is well known that persistent infection by high-risk HPV is the main cause of cervical cancer and its precursor lesions (Hemmat and Bannazadeh Baghi 2019). Circulating IL-6 and IL-10 levels were increased in HPV-positive patients without cervical lesions, but IL-6 levels were higher in exfoliated cervical cells in the same patients, suggesting that IL-6 is mainly produced at the local site of HPV infection during the early inflammatory response and that the immune response changes at the systemic level (Bonin-Jacob et al 2021). The median IL-6 level in HPV-positive patients was 3.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that persistent infection by high-risk HPV is the main cause of cervical cancer and its precursor lesions (Hemmat and Bannazadeh Baghi 2019). Circulating IL-6 and IL-10 levels were increased in HPV-positive patients without cervical lesions, but IL-6 levels were higher in exfoliated cervical cells in the same patients, suggesting that IL-6 is mainly produced at the local site of HPV infection during the early inflammatory response and that the immune response changes at the systemic level (Bonin-Jacob et al 2021). The median IL-6 level in HPV-positive patients was 3.…”
Section: Discussionmentioning
confidence: 99%
“…The local immune environment might be impaired and hence enables viral integration as well as cellular transformation and immortalization. [15][16][17] Cellular lesions resulting from HPV infections are mostly transient as well. For example, when diagnosed with a cervical intraepithelial lesion (CIN) grade 1, 57% and 32% regress or persist, while 12% progress.…”
Section: Introductionmentioning
confidence: 99%
“…The local immune environment might be impaired and hence enables viral integration as well as cellular transformation and immortalization. 15 17 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been some reports on the application of TH1/TH2 cytokines in infectious diseases (5,11,14,17). Many studies have shown that IL-6 and IL-10 are related to infectious disease (18)(19)(20). Some scholars even found that IL-6/ IL-10 could be used to identify G-/G+ bacterial infections in children (15).…”
Section: Discussionmentioning
confidence: 99%